2010
DOI: 10.1007/s00421-010-1673-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of circulating purines and pyrimidines by physical exercise in the horse

Abstract: This study was designed to examine the influence of sub-maximal exercise on purine and pyrimidine catabolism in horses. Ten horses were initially trained for 12 weeks at the end of which they underwent a standardized exercise test (SET); venous blood samples were taken at rest, 5 and 30 min after the SET. Six untrained healthy horses, from which a blood withdrawal was taken at rest, were used as the control group. Samples were analyzed by HPLC for the simultaneous determination of uric acid, uridine, β-pseudou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Changes in metabolites downstream of purine metabolism (inosine, xanthine, urate, allantoin) align with previous studies that reported similar changes in purine metabolites after exercise and attributed them to adenosine triphosphate (ATP) consumption during exercise. , Given the high energy demand associated with high-intensity exercise, these findings are expected after racing. , None of the above-mentioned studies have reported modifications in pyrimidine metabolites. Beyond their role in energy metabolism, both purine and pyrimidine metabolites may serve as regulatory molecules in response to exercise …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in metabolites downstream of purine metabolism (inosine, xanthine, urate, allantoin) align with previous studies that reported similar changes in purine metabolites after exercise and attributed them to adenosine triphosphate (ATP) consumption during exercise. , Given the high energy demand associated with high-intensity exercise, these findings are expected after racing. , None of the above-mentioned studies have reported modifications in pyrimidine metabolites. Beyond their role in energy metabolism, both purine and pyrimidine metabolites may serve as regulatory molecules in response to exercise …”
Section: Discussionmentioning
confidence: 99%
“…Beyond their role in energy metabolism, both purine and pyrimidine metabolites may serve as regulatory molecules in response to exercise. 56 Tricarboxylic Acid Cycle Intermediates. The elevated levels of oxoglutarate and isocitrate, key intermediates in the TCA cycle, following high-intensity exercise, suggest the activation of this metabolic pathway.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulated genes were associated with the pathways of UTP to UDP (3.6.1.5), UDP to UMP (3.6.1.5, 3.6.1.6), UMP to uridine In mammals, when mitochondrial activity is unable to support energy demand, muscles produce ATP through the adenylate kinase reaction in the purine metabolism. The product of purine metabolism is uric acid (82). There are differences in purine metabolism in different species, which cause gout and renal stones in humans, but the effects of which on horses are not known (83).…”
Section: Associations Between Metabolites and Gene Expressionmentioning
confidence: 99%
“…Horses were not involved in an exercise or riding curriculum of any kind, prior to or during the study. Horses were accustomed to individual housing and work on the training mill and treadmill during an adaptation period of 12 weeks, reaching a light-medium fitness level according to previous exercise protocols [10][11]. The daily training during the adaptation period consisted of the following sequence: 5 min walk (approximate speed = 0.8 m/s); 10 min trot M A N U S C R I P T…”
Section: Subjects and Managementmentioning
confidence: 99%